2016
DOI: 10.1016/j.ejps.2015.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response-time modelling: Second-generation turnover model with integral feedback control

Abstract: This study presents a dose-response-time (DRT) analysis based on a large preclinical biomarker dataset on the interaction between nicotinic acid (NiAc) and free fatty acids (FFA). Data were collected from studies that examined dierent rates, routes, and modes of NiAc provocations on the FFA time course. All information regarding the exposure to NiAc was excluded in order to demonstrate the utility of a DRT model. Special emphasis was placed on the selection process of the biophase model. An inhibitory I max -m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Pharmacological data of two intertwined biomarkers and of multiple doses, rates, routes, and schedules were simultaneously regressed. This attests to the view that the success of a DRT analysis is a matter of good experimental design Weiner, 2010, 2016;Andersson et al, 2016) rather than the number of observations, as was recently suggested (González-Sales et al, 2017).…”
Section: A Backgroundmentioning
confidence: 59%
See 1 more Smart Citation
“…Pharmacological data of two intertwined biomarkers and of multiple doses, rates, routes, and schedules were simultaneously regressed. This attests to the view that the success of a DRT analysis is a matter of good experimental design Weiner, 2010, 2016;Andersson et al, 2016) rather than the number of observations, as was recently suggested (González-Sales et al, 2017).…”
Section: A Backgroundmentioning
confidence: 59%
“…These case studies were selected to demonstrate how to tackle baseline/no baseline, time delays, peak shifts, saturation, cell growth/kill data, functional adaptation, rebound, multiple sources of drug provocations and biomarkers, and rapid exposure-response data ( Table 2). Isaksson et al (2009) and Andersson et al (2016Andersson et al ( , 2017 successfully performed meta-analyses on preclinical data on NiAc (nonlinear absorption and elimination)-induced fatty acid lowering, with accurate and precise parameter estimates. The kinetic nonlinearities were well separated from the pharmacodynamic nonlinearities.…”
Section: A Backgroundmentioning
confidence: 99%
“…The PK/PD model applied in this study was derived based on previous models [18, 20, 23], but we added, crucial mechanistic components in order to describe two different kinds of complete adaptation, one seen in lean rats and one in obese. In particular, insulin was included as an endogenous regulator of the turnover of FFA [9].…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between the three models (NiAc, insulin, and FFA) are illustrated in Fig. 1b, and model interactions of previously published NiAc-FFA models [14, 19, 20, 23] are illustrated in Fig. 1a for comparison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation